Home birth integration into the health care systems of eleven international jurisdictions. Issue 3 (13th February 2018) - Comeau, Amanda; Hutton, Eileen K.; Simioni, Julia; Anvari, Ella; Bowen, Megan; Kruegar, Samantha; Darling, Elizabeth K.
Abstract: Background: The purpose of this study was to develop assessment criteria that could be used to examine the level of integration of home birth within larger health care systems in developed countries across 11 international jurisdictions. Methods: An expert panel developed criteria and a definition to assess home birth integration within health care systems. We selected jurisdictions based on the publications that were eligible for inclusion in our systematic review and meta‐analysis on planned place of birth. We sent the authors of the included publications a questionnaire about home birth practitioners and practices in their respective health care system at the time of their studies. We searched published peer‐reviewed, non–peer‐reviewed, and gray literature, and the websites of professional bodies to document information about home birth integration in each jurisdiction based on our criteria. Where information was lacking, we contacted experts in the field from the relevant jurisdiction. Results: Home birth is well integrated into the health care system in British Columbia (Canada), England, Iceland, the Netherlands, New Zealand, Ontario (Canada), and Washington State (USA). Home birth is less well integrated into the health care system in Australia, Japan, Norway, and Sweden. Conclusions: This paper is the first to propose criteria for the evaluation of home birth integration within larger maternity care systems. Application of these criteria across 11 international jurisdictions indicates differences in the recognition and training of home birth practitioners, in access to hospital facilities, and in the supplies and equipment available at home births, which give rise to variation in the level of integration across different settings. Standardized criteria for the evaluation of systems integration are essential for interpreting planned home birth outcomes that emerge from contextual differences.